Penerapan Konsep Crossdocking untuk Menurunkan Persediaan di PT. Coca Cola Distribusi Malang - Ahmad Mubin (Department Industrial Engineering, University of Muhammadiyah Malang, 2003)
This Final duty produce design model distribution system for the finished of problems of product distibution stream. Method which used in system model is method of Crossdocking. Crossdocking used as by method to schedule delivery of product. Ther€ is two step scheduling of delivery, first of scheduling of delivery of factory Sales Center and both scheduling of shipping ofsales Center - outlet. Crossdocking repr€sent distribution melhod as a mean to minimize of is expense of supply, Crossdocking applied by functioned Sales Centar as facility of Crossdock, where at its distribution process of product sent from factory to outlet pass Sales Center without passing inventory storage process. Scheduling of first phase cover amounl, time, target of delivery, and used vehicle. By the end of this system device done by calculation of safety stock as anticipation to avoid stock out to demand of final consumer. Of device model this Crossdockingc an be yielded decrease of inventoryl evel in Sales Center, and decrease of transportation cost from factory to Sales Center.